New sibling species and new occurrences of squat lobsters (Crustacea, Decapoda) from the western Indian Ocean - Macpherson, Enrique; Rodríguez-Flores, Paula C.; Machordom, Annie (European Journal of Taxonomy, 2017)
Numerous specimens of squat lobsters belonging to the families Munididae, Munidopsidae and Eumunididae were collected during several cruises along the eastern coasts of Africa. The study of these specimens revealed the presence of 10 new species (one Eumunida Smith, 1883, eight Munida Leach, 1820 and one Munidopsis Whiteaves, 1874). We describe and illustrate these new species, providing some new data on occurrences and colour patterns for previously described taxa. We have also included molecular data from two mitochondrial markers (16S rRNA and COI) to support the taxonomic status of different species. Some deep-sea species show a clear increase in their geographic range distribution. Finally, a key to known species of the genus Munida from the western and central Indian Ocean is also presented.